Exploration of Students’ Perceptions on the Implementation of Role-Play in German Language Learning - Sobara, Iwa; Putri, Diva Karina; Nurhanna, Marsya Ika; Sahati, Annisa Verdha (Nexus Publishing NXP, 2025)
Roleplay is one of the interactive methods often used in foreign language learning, especially to improve speaking skills. But students may have different preferences about the type of roleplay they enjoy and find effective. In German Language education, roleplay helps students become more confident and fluent in using the language in real-life situations. However, not all types of roleplay work equally well for all learners. Understanding which types of roleplay students prefer can help educators design more engaging and effective learning activities. This study explores the preferences of German language education students at Universitas Negeri Malang regarding different types of classroom roleplay. A Likert-scale survey and in-depth interviews were used to examine preferences in four aspects: pair vs. group roleplay, preferred themes (daily life, academic, or professional scenarios), preferred formats (improvised vs. scripted) and preferred show in (live presentation in class vs. making videotape). The results show that most students prefer to pair roleplay with familiar, everyday themes and a flexible format that combines improvisation and light scripting and prefer to do live presentations in class for the Roleplay. A total of 20 second semester students from Class C participated in a Likert scale questionnaire, and six of them were also interviewed for deeper insight. This study suggests that aligning roleplay activities with student preferences can support more active participation and better language learning outcomes. Future research could further explore how these preferences relate to students' performance and confidence in real communication.